2015
DOI: 10.1063/1.4919822
|View full text |Cite
|
Sign up to set email alerts
|

The abnormal electrical and optical properties in Na and Ni codoped BiFeO3 nanoparticles

Abstract: Bi 0.97 Na 0.03 Fe 1Àx Ni x O 3 (x ¼ 0, 0.005, 0.01, 0.015) nanoparticles are prepared via a sol-gel method. Weak ferromagnetism and exchange bias phenomenon without field cooling are observed in the samples. The oxygen vacancy concentration and leakage current density are increased with increasing the Ni content. However, with the increase of Ni content, the band gap of Bi 0.97 Na 0.03 Fe 1Àx Ni x O 3 nanoparticles first decreases and then increases. To explain the abnormal phenomenon, the interplay of oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…3,4 The optical band gaps of the lms tend to decrease with Ni doping: E g ¼ 2.80 and 2.79 eV are calculated for the samples with 0.5 and 1.0 mol% Ni, respectively. It is plausible that the high concentration of Ni increases the concentration of oxygen-related defect states in the valence-band edge, thereby widening the valence band and thus contributing to narrowing the band gap, 24,26 as suggested by the XPS result shown in Fig. 3(d).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…3,4 The optical band gaps of the lms tend to decrease with Ni doping: E g ¼ 2.80 and 2.79 eV are calculated for the samples with 0.5 and 1.0 mol% Ni, respectively. It is plausible that the high concentration of Ni increases the concentration of oxygen-related defect states in the valence-band edge, thereby widening the valence band and thus contributing to narrowing the band gap, 24,26 as suggested by the XPS result shown in Fig. 3(d).…”
Section: Resultsmentioning
confidence: 95%
“…This result indicates that Ni substitution intensies the oxygenrelated defects, which is consistent with what is observed in other Ni-doped BFO systems. 12,13,24,25 Fig. 4 shows UV-vis transmittance spectra collected from the Ni-BFO lms annealed at 600 C. The transmittance depends on the Ni content.…”
Section: Resultsmentioning
confidence: 99%
“…[28] According to Dario et al, in a similar ABO 3 Perovskite crystal with doping there was a contraction in lattice parameters due to the additional oxygen vacancies created in the system, similar behaviour was also exhibited by zinc doping in BiFeO 3 . [37][38][39] In another study it is reported that doping 2 + ions in the Fe site creates anion vacancies or change the valence state of Fe which in turn leads to the introduction of oxygen vacancies. [40] Figure 2 depicts the results of XPS analysis of the 7.5BFZO sample (a, b, c, and d).…”
Section: Resultsmentioning
confidence: 99%
“…The XRD patterns of Ca 3 Ti 2 O 7 and Ca 3 Ti 1.9 Ru 0.1 O 7 after Rietveld refinement process using FULLPROF software are illustrated in Fig. 1(a) [21]. All peaks in the diffraction patterns could be matched perfectly with those of Ca 3 Ti 2 O 7 (space group A2 1 am (No.…”
Section: Crystal Structure Characterizationmentioning
confidence: 88%